Innenrücktitelbild: Rigid‐Flexible Hybrid Porous Molecular Crystals with Guest‐Induced Reversible Crystallinity (Angew. Chem. 13/2023). (27th February 2023) - Wang, Danbo; Zhao, Yingjie
Abstract : A rigid‐flexible hybrid hydrogen‐bonded organic framework (HOF) with guest‐induced reversible crystallinity was designed by Yingjie Zhao and Danbo Wang in their Research Article (e202217903) . A specific compound, such as hexane, acts as a "key" to control the crystallinity, while the triangle macrocycle as the building module is the "lock". The introduction and removal of the "key" molecule affects the local flexibility of the whole framework and leads to switchable crystallinity.